For Fortune and Glory: A Story of the Soudan War - Hough, Lewis; Paget, Walter, 1863-1935 (Salt Lake City, UT : Project Gutenberg, 2007)
"For Fortune and Glory: A Story of the Soudan War" by Lewis Hough is a historical novel written in the late 19th century. The story interweaves themes of adventure, familial duty, and colonial conflict, centering on young Harry Forsyth who navigates personal challenges amidst the backdrop of the Soudan War. As events unfold, Harry's quest for understanding his family's past and securing his future in a rapidly changing world drives the narrative. At the start of the book, readers meet Harry Forsyth as he returns home from boarding school, eager to reunite with his family. The opening chapters reveal his affection for his mother and sister, as well as the introduction of a mysterious uncle, Ralph Burke, who has returned from living among "wild men" in the desert and brings with him secrets that could alter Harry$1 (Bs life. The story hints at dark familial secrets, particularly regarding a missing will linked to his uncle that has lingering implications for the family's fortune. This blend of personal and historical exploration sets the stage for adventure and moral dilemmas to come as the characters confront their legacies amidst the backdrop of war. (This is an automatically generated summary.)s
Release date is 2007-04-18
Produced by Nick Hodson of London, England
Keywords: Sudan -- History -- 1881-1899 -- Fiction; Great Britain -- History, Military -- 19th century -- Fiction